2019
DOI: 10.1007/s10784-018-09428-1
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability labelling as a tool for reporting the sustainable development impacts of climate actions relevant to Article 6 of the Paris Agreement

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…Moreover, most such studies have focused on the activities of local governments, mainly with respect to a single context and in the same country. This research confirms that reforms carried out within public administrations are influenced by their cultural, political and legal context [2,5,7,17,[30][31][32]49]. However, some researchers have performed comparative analyses of local governments in different countries, and have reported that the explanatory variables of transparency about governmental sustainability (where social and environmental aspects were included) may depend on the administrative culture prevailing in the country (Anglo-Saxon, Southern European or Continental) [2,35,43,50].…”
Section: Prior Research On Local Government Transparency On Sustainabsupporting
confidence: 64%
See 3 more Smart Citations
“…Moreover, most such studies have focused on the activities of local governments, mainly with respect to a single context and in the same country. This research confirms that reforms carried out within public administrations are influenced by their cultural, political and legal context [2,5,7,17,[30][31][32]49]. However, some researchers have performed comparative analyses of local governments in different countries, and have reported that the explanatory variables of transparency about governmental sustainability (where social and environmental aspects were included) may depend on the administrative culture prevailing in the country (Anglo-Saxon, Southern European or Continental) [2,35,43,50].…”
Section: Prior Research On Local Government Transparency On Sustainabsupporting
confidence: 64%
“…However, although an increasing amount of research is being conducted in this area, most studies have addressed the private sector, while our understanding of sustainability (including social and environmental aspects) and information disclosure in the public sector remains at an initial stage of development [47,48]. Among the studies that have been conducted, many conclude that public agencies often disclose insufficient financial information and that citizens require more information in this respect, as part of a new approach that also includes social and environmental information [5,19,20,30]. Moreover, most such studies have focused on the activities of local governments, mainly with respect to a single context and in the same country.…”
Section: Prior Research On Local Government Transparency On Sustainabmentioning
confidence: 99%
See 2 more Smart Citations
“…The information could be either stored as metadata [63], or by using non-fungible tokens. Recent discussions on how to measure and quantify the different SDG impacts [44,64,65] may create the foundation for such information to be added to a digital information system like blockchain.…”
Section: Unit Quality and Information Asymmetrymentioning
confidence: 99%